Kinetics and Thermodynamics Study of Ultrasound-Assisted Depolymerization of k-Carrageenan in Acidic Solution - Ratnawati Ratnawati; Nita Indriyani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
K-carrageenan is a natural polymer with high molecular weight ranging from 100 to 1000 kDa. The oligocarrageenan with low molecular weight is widely used in biomedical application. The aim of this work was to depolymerize k-carrageenan in an acidic solution with the assistance of ultrasound irradiation. The ultrasonication was conducted at various pH (3 and 6), temperatures (30-60 °C), and depolymerization time (0-24 minutes). The results show that the depolymerization reaction follows pseudo-first-order kinetic model with reaction rate constant of 1.856×10-7 to 2.138×10-6 s-1. The reaction rate constant increases at higher temperature and lower pH. The Q10-temperature coefficients of the depolymerization are 1.25 and 1.51 for pH 6 and 3, respectively. The enthalpy of activation (ΔH‡) and the Gibbs energy of activation (ΔG‡) are positive, while the entropy of activation (ΔS‡) is negative, indicating that the activation step of the ultrasound-assisted depolymerization of k-carrageenan is endothermic, non-spontaneous, and the molecules at the transition state is more ordered than at the ground state. The ΔH‡ and the ΔS‡ are not affected by temperature, while the ΔG‡ is a weak function of temperature. The ΔH‡ and ΔS‡ become smaller at higher pH, while the ΔG‡ increases with the increase of pH. The kinetics and thermodynamics analysis show that the ultrasound-assisted depolymerization of k-carrageenan in acidic solution is possibly through three mechanisms, i.e. bond cleavage due to cavitational effect of microbubbles, hydroxyl radical and hydrogen peroxide, as well as proton. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).